Perubahan Kualitas Beberapa Klon Harapan Ubi Jalar (Ipomoeabatatas L.) Hasil dari Dua Lokasi Penanaman Selama Penyimpanan - Fakhry, Muhammad (Universitas Trunojoyo Madura, 2008)
The research aims to investigate the changes of the quality of several clones of sweet pota fo planted in two sites. The clone of 1-57,IR, CN 1332-2, 73-6, 73-6/l,and 73-6,12 was planted at Telang, Bangkalan located 5 m above sea level and at Batu, Malang located 600 m above sea level. Theharvestfrom two sites above was then·storaged in a room inMalang whithout temperature arrangementfor 60 days. The treatments were arranged ina complete randomize with three replications. ·Results showed that clone IRfrom Malang had longer storaged life compared to clone 1-57, CN 1332-2, 73-6, 73-6/l, and 73-6,1.2. It was characterized by the changes of water contentfrom 0,96% to 3 % and the changes in respiration ratefrom 5,8% to 83,1%. Clone 73-6,l.2from Bangkalan had better storage life compared to clone 1-57, IR, CN 1332-2, 73- 6,and 73-6/l. Also this clone had starch contentfrom 10,6% to 21,3% .It can be concluded that clone IR is suitable for upland areas while clone 73-6,1.2 is suitable for lowland area. Moreover, toexamine consumer preference to the storaged tuber, an organoleptic test should beemployed.